Memahami Peribahasa "Nai Ngalis Tuka Ngengga" dalam Budaya Hambor Manggarai melalui Konsep Otentisitas Martin Heidegger: Kontribusi terhadap Kesadaran Perdamaian - Wenseslaus Jugan; Pius Pandor (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The main focus of this article is to explore the wealth of wisdom encapsulated in the proverb "Nai Ngalis Tuka Ngengga," which is ingrained in the culture of Hambor Manggarai. The goal of this writing is to make the local wisdom of Nai Ngalis Tuka Ngengga in the Hambor Manggarai culture a philosophical study to enhance the awareness of Indonesian society in living and interpreting their being in the midst of the community, particularly in embracing a narrative of peace. The concept of authenticity by Martin Heidegger emphasizes how Dasein, which is the human being aware of its existence in the world, plays a role in this context. In the exposition on authenticity, authentic Dasein becomes the answer to human forgetfulness of its existence in the world. In this context, "Being" describes the wisdom of the Manggarai people in understanding and embracing the Hambor culture in their daily lives. The research methodology used in this study is qualitative research with a literature review approach. The research findings indicate that the proverbial wisdom in embracing Hambor culture represents authentic consciousness in the community's celebration of the narrative of peace. This research contributes to addressing the conflicts present in society today, such as identity politics, conflicts related to the construction of places of worship, and widespread human rights violations due to a lack of understanding of the meaning of Hambor culture.